Quality of maternal and newborn hospital care in Brazil: a quality improvement cycle using the WHO assessment and quality tool. (23rd February 2021) - Pessa Valente, Emanuelle; Barbone, Fabio; de Melo E Lima, Tereza Rebecca; de Mascena Diniz Maia, Paula Ferdinanda Conceição; Vezzini, Francesca; Tamburlini, Giorgio
Abstract: Background: Increasing efforts toward quality improvement (QI) are necessary in low- and middle-income countries (LMICs) to reduce maternal and perinatal mortality and morbidity and to promote respectful care. In Brazil, perinatal health indicators are below targets in several states despite universal access to perinatal services and very high rates of institutional births, indicating poor quality of care (QoC) as a key issue to be addressed. However, research efforts to develop and test QoC improvement interventions are scarce. Objectives: We assessed the effects of a 1-year comprehensive QI cycle using a World Health Organization (WHO) assessment and quality tool on maternal and newborn care at hospital level and documented QIs obtained after a 1-year comprehensive QI cycle. Methods: Uncontrolled, unblinded, pre–post study carried out in six maternity hospitals in Pernambuco, Brazil, accounting for 29 128 live births in 2014. A standards-based and participatory approach based on a WHO quality assessment and improvement tool for maternal and neonatal care at hospital level was used. A national team of assessors supervised by international experts carried out baseline and final assessments. An action plan was developed and implemented to address key quality gaps emerging from the baseline assessment and from two supportive supervision visits. Results: At baseline, hospitals presented a variety of quality gaps, the majority common to all participating centers. Gaps in case management of normal and complicated deliveries and in respectful and holistic care were predominant, in both teaching/tertiary and secondary care hospitals. After one year, several improvements were observed, particularly in respectful care during labor and at delivery, in case management of normal labor and delivery and in neonatal care. Conclusions: A systematic participatory approach based on a WHO tool produced important QIs in a relatively short time and should be considered for use for large-scale QI programs in Brazil and other LMICs. Its comprehensive, peer-to-peer and action-oriented nature and its capability to document QI over time and to build a QI culture represent important comparative advantages over other QI interventions.